Hi-de-ho the life of Cab Calloway - Shipton, Alyn 1953- (Oxford University Press, 2010)
This title sheds new light on Cab Calloway's life and career, explaining how he traversed racial and social boundaries to become one of the country's most beloved entertainers. Drawing on first-hand accounts from Calloway's family, friends, and fellow musicians, the book traces the roots of this music icon, from his childhood in Rochester, New York, to his life of hustling on the streets of Baltimore.